Comparative study of vaginal hysterectomy and abdominal hysterectomy for enlarged uterus - S., Chandrika; Kosti, Kasinath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the second most common gynecological surgeries performed. Maximum (70% to 80%) hysterectomies are done by abdominal route. Abdominal route provides good visibility and easy access to pelvic organs. Methods: Randomized prospective comparative study was carried out to know the feasibility of vaginal hysterectomy in moderately enlarged uterus due to benign conditions and to compare operative complications and morbidity of vaginal and abdominal hysterectomy in moderately enlarged uterus due to benign conditions at Department of Obstetrics and Gynecology, at tertiary health care hospital during the period from October 2009 to September 2011. Results: Out of 50 cases, 25 cases were subjected for abdominal hysterectomy and 25 for vaginal hysterectomy. Cases with moderately enlarged uterus up to 16 weeks due to benign condition were included in the study. Cases with uterus more than 16 weeks, previous pelvic surgeries, adnexal mass, prolapse and restricted mobility were excluded from our study Conclusions: Bulk reducing techniques were used to remove the moderately enlarged uterus through vaginal route. Vaginal hysterectomy is invasive route, safe and feasible in cases with enlarged uteri up to 14 weeks due to benign causes.